2000
DOI: 10.1038/sj.bjp.0703584
|View full text |Cite
|
Sign up to set email alerts
|

Inverse agonism and neutral antagonism at a constitutively active alpha‐1a adrenoceptor

Abstract: 1 We have studied the antagonist action of prazosin and KMD-3213 in a constitutively active mutant of the human alpha-1a adrenoceptor in which Ala 271 was substituted to Thr and was expressed in CHO cells. Inverse agonism was characterized by up-regulation of receptor density, a decrease in basal GTPgS binding, and a reduction in basal inositol-1,4,5-trisphosphate (IP 3 ) level. 2 According to the above criteria, prazosin acted as an inverse agonist, whilst KMD-3213 behaved as a neutral antagonist. 3 Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…It was shown that inverse agonists could induce the internalization of the CCK A receptor (Roettger et al, 1997), although increased cell surface expression has been reported for other receptors after inverse agonist treatment (Smit et al, 1996;Lee et al, 1997;Zhu et al, 2000). Our results showed that none of the three more potent inverse agonists (Montelukast, MK571, and Zafirlukast) induced receptor sequestration; rather, they all promoted cell surface expression.…”
Section: Inverse Agonists Of the Cyslt 1 Receptor 105mentioning
confidence: 34%
See 1 more Smart Citation
“…It was shown that inverse agonists could induce the internalization of the CCK A receptor (Roettger et al, 1997), although increased cell surface expression has been reported for other receptors after inverse agonist treatment (Smit et al, 1996;Lee et al, 1997;Zhu et al, 2000). Our results showed that none of the three more potent inverse agonists (Montelukast, MK571, and Zafirlukast) induced receptor sequestration; rather, they all promoted cell surface expression.…”
Section: Inverse Agonists Of the Cyslt 1 Receptor 105mentioning
confidence: 34%
“…Our results showed that none of the three more potent inverse agonists (Montelukast, MK571, and Zafirlukast) induced receptor sequestration; rather, they all promoted cell surface expression. Increased receptor expression has usually been seen after prolonged treatment of cells with the inverse agonists and possibly implicated the activation of cellular pathways, resulting in resensitization and up-regulation of receptor expression (Smit et al, 1996;Lee et al, 1997;Zhu et al, 2000). However, this would not apply 6.…”
Section: Inverse Agonists Of the Cyslt 1 Receptor 105mentioning
confidence: 99%
“…Prazosin has been shown to be an inverse agonist of ␣ 1A -and ␣ 1B -ARs (Rossier et al, 1999;Zhu et al, 2000), whereas KMD-3213 is an ␣ 1A -AR-selective neutral antagonist (Zhu et al, 2000;Zhang et al, 2002). Therefore, it is likely that ␣ 1A -and ␣ 1B -ARs and their combined expression in HEK 293 cells have little constitutive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they reported a lack of upregulation of this CAM form when using KMD-3213, which they indicated to be a neutral antagonist (Zhu et al, 2000), suggesting a possible means to discriminate between neutral and inverse agonist ligands. Although intriguing, the basis for these di erences were not established and the e cacy of KMD-3213 was very similar to that of BMY7378, which did produce strong upregulation (Zhu et al, 2000).…”
Section: British Journal Of Pharmacology Vol 133 (2)mentioning
confidence: 99%
“…Interestingly, Zhu et al (2000) have recently observed that sustained treatment with a variety of ligands which function as inverse agonist at a CAM form of the human a 1a -adrenoceptor produces substantial upregulation of the mutant but not the wild-type receptor. Moreover, they reported a lack of upregulation of this CAM form when using KMD-3213, which they indicated to be a neutral antagonist (Zhu et al, 2000), suggesting a possible means to discriminate between neutral and inverse agonist ligands. Although intriguing, the basis for these di erences were not established and the e cacy of KMD-3213 was very similar to that of BMY7378, which did produce strong upregulation (Zhu et al, 2000).…”
Section: British Journal Of Pharmacology Vol 133 (2)mentioning
confidence: 99%